Reviewing the Potential of Phase Change Materials in Concrete Pavements for Anti-Freezing Capabilities and Urban Heat Island Mitigation - Iman Asadi; Stefan Jacobsen; Mohammad Hajmohammadian Baghban; Mehdi Maghfouri; Mohammad Hashemi (Buildings, 2023)
This study provides an overview of how phase change materials (PCMs) can improve the resistance of concrete pavement to freeze–thaw cycles and mitigate the urban heat island (UHI) effect. The investigation covers different types of PCMs and methods for integrating them into concrete pavement, as well as the mechanical properties and compressive strength of concrete pavement when employing various PCMs. Prior studies have identified porous aggregates, microencapsulation, and pipelines containing liquid PCM as common approaches for PCM integration. Researchers have observed that the utilization of PCMs in concrete pavement yields favorable thermal properties, suggesting the potential for anti-freezing and UHI mitigation applications. However, the choice of PCM materials should be informed by local climate conditions.